Awareness Among the Undergraduate Dental Students Regarding Computer Aided Design and Computer Aided Manufacturing Technology in Various Universities at Makkah Region, Saudi Arabia- A Questionnaire-Based Study: Life Sciences-Dental Science - Shetty, Dr. Karunakar; A Balkhyoor, Dr. Jood Ahmed; M Hamdi, Dr. Suzan Sami; Aloufi, Dr. Ghadi Turki; Abdullah Amer, Dr. Nura (International Journal of Life Science and Pharma Research, 2022)
Demand for the esthetic dentistry has abundantly increased and due to that metal free ceramic became very popular. That is why most of the practitioners started using CAD/CAM technology, so that they can save time and get a reliable product which has pleasing esthetic and functional results. Most of the researchers have focused on dental practitioners and not many studies on undergraduate dental students. Hence, our aim was to find out the knowledge and awareness among the dental undergraduate students and interns regarding CAD/CAM technology and objective was to provide platform for the undergraduate dental students regarding utilization of CAD/CAM Technology in the future. A cross-sectional, Questionnaire based study was conducted among dental students, covering various Dental colleges in Makkah region. The non- probability convenience sampling technique will be used for calculating the appropriate sample size. Total sample for this study was 303. The closed ended questionnaire was constructed by the authors consisting of 19 questions. Pilot study was conducted on 20 dental undergraduate students. Statistical Package for Social Sciences version 20 was used to perform the statistical analysis. Data was entered in the excel spread sheet. Inferential statistics like Chi-square test was applied for qualitative variables to find the association. The level of significance is set at 5%. This study included 303 participants, out of which78 (25.7%) participants were dental interns and 225 (74.3%) dental students. Among the dental students, 65 (21.5%) participants were 4th year students, 66 (21.8) participants were 5th year students and 94 (31%) participants were 6th year students. Among the participants, 67 (85.9%) of the interns and 215 (95.6%) of the students were aware of the CAD/CAM technology. The majority of study participants were in the favor that CAD/CAM fabricated restorations are much better than those conventionally fabricated restorations and advised to include CAD/CAM technology in the curriculum.